Pengaruh Pemberian Aromaterapi Lavender Terhadap Kualitas Tidur Lansia di UPT RPS Lanjut Usia Budhi Dharma Yogyakarta: Pengaruh Pemberian Aromaterapi Lavender Terhadap Kualitas Tidur Lansia Di UPT RPS Lanjut Usia Budhi Dharma Yogyakarta - Fauziah, Syifa; Suib, Suib (Ruang Ide Publisher, 2024)
Background: Aging is a natural process, one that will occur in all human systems and is characterized by progressive degeneration of both physical and psychic systems that will impact the quality of sleep. In older age these sleep mechanisms occur longer because of inability to start sleep, to maintain sleep, to get up early or to wake up with discomfort. One way to overcome the problem of sleep disorders is to use complementary therapy with aromatherapy. The effect of personal aromatherapy can be soothing and relaxing. Among the frequent aromatherapy is that lavender scent is commonly used to lower stress levels, headaches, burns, or lesions, muscle relaxant, and improve sleep quality. The purpose of this study is to understand the effects lavender's scent on the quality of sleep in the aged budhi dharma Yogyakarta. Methods: this type of research is an experimental quantitative study using pre exam design (one group pre test and post design test). Research is conducted on the upt RPS of the elderly budhi dharma yogykarta. The study's population is 60-76 years old and lives in homes of 61 people. The number of samples was 17 respondents with a total sampling technique. The instrument of this study uses the Pittsburgh sleep quality index (PSQI) questionnaire. Data analysis method Paired t-test specimen. Results: studies show that there is a significant difference in the quality of sleep for a respondents after lavender aromatherapy is given. This is proven by the independent t test, on the acquisition of p-value sleep quality 0,000 or 0.05.Conclusion: it may be concluded that there was a significant impact on the quality of sleep of the respondents after lavender aromatherapy was administered.